Nel.lo, Oriol (2012). Ordenar el territorio. La experiencia de Barcelona y Cataluña - Vicente Rufí, Joan (Documents d'Anàlisi Geogràfica, 2014)
Nel·lo, Oriol (2012). Ordenar el territorio. La experiencia de Barcelona y Cataluña València, Tirant Humanidades, Colección Crónica, 256 p. ISBN 978-84-15442-46-2